Uncovering the Function of MBP and Antibiotics in Preventing Surgical Site Infections during Colorectal Procedures - Shibu, Agnes Sara; Raj, Rojin G.; Singh Deo, Rohit (Journal of Coloproctology, 2024)
Introduction Surgical site infections (SSIs) remain a significant concern in colorectal surgery, impacting patient outcomes and healthcare costs. Mechanical bowel preparation (MBP) and antibiotic prophylaxis are widely used strategies to reduce the incidence of SSIs. However, their effectiveness and the associated risks continue to be topics of debate within the medical community. This review aims to assess the current evidence on the use of MBP and antibiotics in preventing SSIs during colorectal procedures, highlighting the benefits, controversies, and ongoing discussions in the field.Objective This review evaluates the effectiveness and controversy surrounding the use of mechanical bowel preparation (MBP) and antibiotic prophylaxis in preventing surgical site infections (SSIs) during colorectal procedures.Methodology The review looks at a variety of research, such as meta-analyses and trials, and examines the timing, choice of antibiotics, and various facets of MBP. Findings Prophylactic antibiotic use considerably lowers SSIs; however, resistance issues are raised. MBP works well, but there are debates over the risks involved. With continuous discussions, combined antibiotic-MBP methods are prevalent.Conclusion the evaluation acknowledges the potential for prevention but emphasizes the need for careful use that takes patient variables into account. Optimal techniques are the subject of ongoing study, which emphasizes the dynamic nature of SSI prevention in colorectal surgery.
Keywords: mechanical bowel preparation; oral antibiotics; surgical site infections; colorectal; surgery; antibiotic resistance